Virulence of entomopathogenic fungi against nymphs of Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae) - Potrich, Michele (2011)
The objective of this study was to evaluate the pathogenicity and virulence of isolates of Beauveria bassiana (Unioeste 47 and Unioeste 57), Metarhizium anisopliae (Unioeste 43 and Esalq 09) and Isaria sp. (IBCB 367 a d IBCB 394) against Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae). Suspensions of the isolates (1.0 × 109 conidia/mL) were sprayed on third instar nymphs on cabbage leaves. It was performed four replications, each one with 20 insects, for each treatment. The control consisted of sterile distilled water + Tween® 80 (0.01%). The number of killed nymphs was evaluated during seven days, and then they were kept in a moist chamber. To estimate the median lethal concentration (LC50), isolates suspensions of 1.0 × 105, 1.0 × 106, 1.0 × 107, 1.0 × 108 and 1.0 × 109 conidia/mL were sprayed on third instar nymphs. The number of nymphs with confirmed mortality was evaluated. The isolates B. bassiana Unioeste 47 (84.1%) and Isaria sp. IBCB 367 (98.6%) did not differ significantly, causing the highest mortalities. However, the isolate M. anisopliae Esalq 09 caused the lower confirmed mortality (23.2%). The LC50 of the B. bassiana isolates varied from 1.8 × 105 and 4.1 × 105 conidia/mL (Unioeste 57 and Unioeste 47, respectively). Among the isolates of M. anisopliae, Esalq 09 presented the highest LC50 value (7.8 × 108 conidia/mL), whereas Unioeste 43 presents the lowest (4,3 × 105 conidia/mL). The Isaria sp. isolates presented LC50 of 2.5 × 105 and 3.1 × 105 conidia/mL (IBCB 367 and IBCB 394, respectively). Therefore, B. bassiana Unioeste 47 e Isaria sp. IBCB 367 isolates had potential to B. tabaci control and for future field studies.